Efektivitas Penerapan Etika Politik Islam terhadap Regulasi Pemerintah Terkait Pemberdayaan Perempuan - Syukkur, Abdul; Angraini, Emilia (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2024)
This research reviews the effectiveness of applying Islamic political ethics to government regulations related to women's empowerment. This is important to do because there is a need for in-depth study of how Islamic political ethics can be effectively applied to support and strengthen government regulations in empowering women. So that various problems such as gaps between genders, gender bias, negative stigmatization of women, and forms of violence and harassment against women will no longer occur. The method used in this research is library research using qualitative data analysis techniques, which produces analytical descriptive data. This research succeeded in exploring the interaction between the principles of Islamic political ethics, government policy, and social reality in efforts to empower women. Key words: Islamic political ethics, government regulations, women's empowerment.